The Sea floor / produced by Intelecom. - Sadd, James; Gilfillan, David (Earth revealed, 1992)
Looks at the research by submersibles and indirect methods used to study the bottom of the sea, providing a glimpse of volcanic activity, formations such as the continental shelf and mid-ocean ridges, and life forms that thrive at extreme depths.